Adverse maternal outcomes and birth weight discordance in twin gestation: British Columbia, Canadian data - Jahanfar S; Lim K (Dove Medical Press, 2017)
Shayesteh Jahanfar,1 Kenneth Lim2 1Department of Community Health, Central Michigan University, Mount Pleasant, MI, USA; 2Division of Maternal Fetal Medicine, British Columbia Women’s Hospital, Vancouver, BC, Canada Objective: The aim of this study was to determine whether twin pregnancies with birth weight discordance were associated with higher rates of maternal morbidities.Study design: A large retrospective population-based cohort study of twins born in British Columbia, Canada, from 2000 to 2010 was performed. Maternal morbidities and growth discordant were evaluated.Results: There were 6,328 twin deliveries during the study period. Pregnancies carrying growth-discordant twins had higher frequencies of hypertension disorders, preterm labor, and cesarean delivery compared with growth-concordant twins. They also stayed longer than 3 days in hospital. Multivariate generalized estimating equation modeling found higher odds of preeclampsia, pregnancy-induced hypertension, preterm delivery, and cesarean delivery in mothers carrying growth-discordant twins compared with those carrying growth-concordant category. The modeling also resulted in higher odds in the length of stay longer than 3 days in mothers carrying growth-discordant twins compared with those carrying growth-concordant twins after adjustment for chorionicity.Conclusion: Maternal complications are associated with growth discordance. Screening for birth weight discordance during pregnancy may alert clinicians to predict subclinical maternal conditions. Keywords: length of stay, retrospective, maternal morbidity